Safety and aesthetic outcomes of double purse-string suture nipple reconstruction in early breast cancer patients undergoing nipple resection and endoscopic skin-sparing mastectomy with breast reconstruction - Dai, Hui; Chung, Kawun; Liang, Faqing; Xie, Yanyan; Zhang, Qing; Qiu, Mengxue; Yang, Huanzuo; Zhou, Jiao; Feng, Yu (Frontiers in Oncology, 2024)
BackgroundThe current surgical methods for managing incisions after nipple excision in breast reconstruction patients are limited. However, double purse-string suture (DPS) shows promise in the treatment of nipple excision. This study aimed to investigate the safety and aesthetic outcomes of DPS nipple reconstruction in early breast cancer patients who underwent endoscopic skin-sparing mastectomy (E-SSM) and breast reconstruction.MethodsWe retrospectively analyzed the clinical data of 87 early breast cancer patients with nipple excision who underwent E-SSM with breast reconstruction. According to the suture methods of nipple incision, all patients were divided into the spindle suture (SS) group, single purse-string suture (SPS) group, and DPS group, with SS and SPS groups combined as the traditional suture (TS) group. Then, we compared the groups’ differences in aesthetic outcomes, surgical safety, and oncological safety.ResultsA total of 87 patients with 88 breasts were enrolled in this study (SS n=17, SPS n=21, DPS n=50). Patients in the DPS group had significantly better nipple reconstruction satisfaction, Harris scale and any complications incidence than the TS group (all p <0.05). For nipple reconstruction satisfaction and any complication, the adjusted OR (95%CI) of the DPS group were 6.314(1.095-36.415) (p=0.039) and 0.124(0.018-0.863) (p=0.035) compared with the SS group. One patient in the SS group had vertebral metastases, and no recurrence, metastasis, or death has been observed in the other two groups during the follow-up period.ConclusionsDPS is an effective and safe nipple reconstruction procedure for patients undergoing E-SSM with breast reconstruction, delivering excellent aesthetic outcomes.